AN OPEN TRIAL OF INTEGRATIVE THERAPY FOR GENERALIZED ANXIETY DISORDER - Newman, Michelle G. (2008)
Cognitive– behavioral therapy (CBT), although effective, has the lowest average effect size for generalized anxiety disorder (GAD), when compared to effect sizes of CBT for other anxiety disorders. Additional basic and applied research suggests that although interpersonal processes and emotional avoidance may be maintaining GAD symptomatology, CBT has not sufficiently addressed interpersonal issues or emotion avoidance. This study aimed to test the feasibility and preliminary efficacy of an integrative psychotherapy, combining CBT with techniques to address interpersonal problems and emotional avoidance. Eighteen participants received 14 sessions of CBT plus interpersonal emotional processing therapy and three participants (for training and feasibility purposes) received 14 sessions of CBT plus supportive listening. Results showed that the integrative therapy significantly decreased GAD symptomatology, with maintenance of gains up to 1 year following treatment. In addition, comparisons with extant literature suggested that the effect size for this new GAD treatment was higher than the average effect size of CBT for GAD. Results also showed clinically significant change in GAD symptomatology and interpersonal problems with continued gains during the 1-year follow-up. Implications of these results are discussed.